2018
DOI: 10.1016/j.cej.2018.03.058
|View full text |Cite
|
Sign up to set email alerts
|

A techno-economic assessment of the potential for combining supercritical water oxidation with ‘in-situ’ hydrothermal synthesis of nanocatalysts using a counter current mixing reactor

Abstract: A techno-economic assessment of the potential for combining supercritical water oxidation with 'insitu' hydrothermal synthesis of nanocatalysts using a counter current mixing reactor, Chemical Engineering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The organic molecules are easily attacked by hydroxyl radicals which are produced during the Fenton reactions. The present study results indicated that the addition of a small amount of dissolved iron salt to H 2 O 2 solution that might increase the performance of SCWO on the degradation of acrylic acid, which play a synergistic role in the Fenton oxidation and SCWO at relatively moderate reaction temperature (Al-Atta et al 2018 ).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…The organic molecules are easily attacked by hydroxyl radicals which are produced during the Fenton reactions. The present study results indicated that the addition of a small amount of dissolved iron salt to H 2 O 2 solution that might increase the performance of SCWO on the degradation of acrylic acid, which play a synergistic role in the Fenton oxidation and SCWO at relatively moderate reaction temperature (Al-Atta et al 2018 ).…”
Section: Introductionmentioning
confidence: 72%
“…The reaction temperature was set to exceed the critical point of water which is governed by heater limitation. A short residence time was chosen because it was shown to have very little effect on the oxidation of other compounds like acrylic acid (Al-Atta et al 2018 ). The results of the preliminary experiments in terms of the removal of phenol and COD are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that the HEPP plants will able to use their own process waste as fuel if not entirely on their own but with integration into hybrid processes that will generate energy as well as energy recovery and material products from waste (see for example Al-Atta et al, 2018).…”
Section: Discussion Of Potential Hybrid Energy Process Plant Applicatmentioning
confidence: 99%
“…e software allows, also, the use of available broad database of chemicals and physical parameters that permit built-in operation units suitable for sensitivity analysis and modelling of various processes related to petrochemicals [28], catalysts [29], hydrogen production [30], and carbon dioxide capture [31]. e application of Aspen Plus was reported in the field of nanotechnology [32,33]; however, it should be pointed out that, to the best of our knowledge, this approach has never been used for investigating such nanomaterials synthesis. Hence, the present work is devoted to sensitivity analysis and simulation of large-scale production of molybdenum disulfide nanoparticles, using Aspen Plus.…”
Section: Introductionmentioning
confidence: 99%